Planning and Review Days on Participatory Integrated Climate Services for Agriculture (PICSA) Rollout, Balaka District, Malawi, 26-27 October 2015 - Kafasalire A; Nyirongo D (2016)
The purpose of the Planning and Review meeting was to review the rollout of the Participatory Integrated Agriculture Climate Services (PICSA) process with intermediaries from the Ministry of Agriculture, Irrigation and Water Development (MoAIWD); Malawi Red Cross (MRC); and Concern Universal. National government staff from the Department of Disaster and Management Affairs (DoDMA), Department of Agriculture and Extension Service (DAES), and Planning Department within the Ministry of Agriculture Irrigation and Water Department. At the district level, representatives of Balaka District Council (BDC) attended the meeting. The meeting was organized by WFP in collaboration with CCAFS, DCCMS, MRC, University of Reading and MoAIWD. The meeting helped the participants to refresh their knowledge and skills in delivering the PICSA training material to farmers in Balaka, Lilongwe and Nsanje Districts. Meeting participants were able to identify difficult aspects of the PICSA concept during the trainings with farmers and a refresher was provided to help them master the trainings. Apart from this, intermediaries were able to learn from each other as they shared their experiences during the trainings. Presentations and discussions on a downscaled seasonal forecast, and ICT- and radio-based communication, helped participants to complement their skills and knowledge base in providing climate services to farmers. Several recommendations came out of the meeting. First, WFP and CCAFS should continue engaging stakeholders, including Ministry of Agriculture, Malawi Red Cross and Concern Universal, to continue to provide training material, technical support to intermediaries as they rollout the PICSA approach. Second, technical words in the PICSA manual should be translated for use by the intermediaries. Third, discussions around institutionalizing the PICSA concept as well as the Planning and Review meetings in the sector plans and activities should be prioritized and nurtured by all stakeholders. Fourth, in the future, large groups of intermediaries should be split into two for the P&R workshops, but each group would still stay for two days of meeting. Fifth, refreshments and allowances were seen as unsustainable incentives for participation, and set a bad precedence for other community programmes. Sixth, since PICSA is intended to be assimilated into the extension workers’ jobs, there is need to continue engaging the district officials (supervisors) to pass the same message to extension workers, and follow up to ensure this is happening. Seventh, continue discussing this issue of incentives with stakeholders, considering the fact that some topics in the PICSA training content take longer than a day to cover, and therefore require keeping farmers longer. Finally, there was a recommendation to conduct regular follow up meetings with both intermediaries and farmers in order to help in building their capacity in utilizing climate services.